Produção do espaço, planejamento e mobilidade urbana: o uso da bicicleta como meio de transporte em Natal - Torres, Leo Selva Ortencio Silva (2018)
This work has the intention to show Natal’s municipality space production in a historic perspective, as well as, its relation with the urban mobility, to understand the insertion of the cycle modal in this context. For this, analysis was made in the evolution of Natal urban space, in the transports in a world, Brazilian and local level, as well as, in Brazilian and Natal Master Plans. For the bicycle usage understanding in the urban environment, a bibliographic research has been made in the search of understanding about how this vehicle has been used since its invention in the world wide main cities as well as Brazilians ones. In Natal the approach about cycling advocacy has been watched in a more recent temporal space, in interviews, document and bibliographic sources analyses, cyclists counting in strategic city spots and the evaluation of the cycle paths spread in Natal municipality. The urban space production, was found to follow a logic that attend the interests of hegemonic groups, similarly, the road infrastructure follows this same logic. Therefore, in Natal context, the bicycle as an urban transport and its inclusion on the mobility policy has occurred only after the 2010s, although hesitantly. Even with the increasing of cycle paths in the last two years, many of them are suboptimal, despite being insufficient. As result, bicycling as transport in Natal still quite limited. Finally, its recommended more cycle path investment and more educative campaign directed to the cyclists, as well as, the planning of a new bicycle path system to Natal and the Metropolitan Region main cities.